Addressing educational disparities: the role of policy in expanding early childhood education access in 3T areas - Sari, Putri Indah; Rudiyanto, Rudiyanto; Agustin, Mubiar (Tunas Siliwangi, 2024)
Poor health can hinder a child''s overall development. Inadequate stimulation at home: Many children do not receive enough cognitive stimulation and emotional support in their early years, which are critical for brain growth and learning. The research method used in this article is a literature study by collecting books, journal articles, research reports, and other sources relevant to the topic of The Role of Policy in Building Equitable Access to Early Childhood Education. There are many ways that the budget for ECE operations can be used to improve early childhood education, such as: 1) Improved Facilities and Infrastructure: With sufficient budget, ECE institutions can repair and upgrade their physical facilities that support learning, such as libraries, playgrounds, and classrooms. 2) Improving the Quality of Educators: To improve the quality of teaching and learning in ECE, an adequate budget can be used for training and development of ECE teachers to meet teacher competency standards. This will have a positive impact on the quality of teaching and learning in ECE. 3) Curriculum Development and Learning 4) Procurement of Teaching Materials and Learning Media: You can use the budget to purchase high-quality teaching materials and learning media It is important that action is taken by the government to address disparities in access to education in disadvantaged, frontier and outermost (3T) areas